TAHAP BRAHMACARI ASRAMA PIJAKAN MENUJU TAHAP KEHIDUPAN SEJAHTERA DAN BERKUALITAS - Ni Wayan Sumertini (Sanjiwani: Jurnal Filsafat, 2018)
Hinduism recognizes the teachings of Catur Ashrama. Teachings of Catur Ashrama consists of Brahmacari, Grhasta, Wanaprastha, and Biksuka. Brahmacari is one of the most important things in the lives of children. At this level, man are at the learning stage. More and more age to learn. There is a science of art and technology that must be studied for the provision to the next stage of life. There is a religious ethic that must be occupied and lived as a life guide. There are many good things for formal, informal and non-formal education. The Brahmacari concept is a Hindu teaching in need in the Vedic scriptures that is very sublime for us to practice. The Brahmacari concept provides an explanation of the meaning of education for all of us who will impact on growth or bring benefits for ourselves, society and nation. Brahmacari is the only concept that is excellent and qualified.